Ultra-rapid flow cytometry assay for colistin MIC determination in Enterobacterales, Pseudomonas aeruginosa and Acinetobacter baumannii. (November 2020) - Fonseca e Silva, Daniela; Andrade, Ferdinando F.; Gomes, Rosário; Silva-Dias, Ana; Martins-Oliveira, Inês; Pérez-Viso, Blanca; Ramos, Maria Helena; Rodrigues, Acácio G.; Cantón, Rafael; Pina-Vaz, Cidália
Abstract: Objectives: Both EUCAST and CLSI recommend broth microdilution for antimicrobial susceptibility testing of colistin, but this method is cumbersome and takes 16-24 h to give results. Our objective was to evaluate a rapid quantitative colistin MIC susceptibility assay based on flow cytometry analysis (FASTcolistin MIC) in comparison with standard broth microdilution assay. Methods: One hundred and sixteen Gram-negative bacilli (78 Enterobacterales, 28 Pseudomonas aeruginosa and 10 Acinetobacter baumannii) were studied in parallel using standard broth microdilution following EUCAST recommendations and FASTcolistin MIC kit. In the last one, a bacteria suspension (0.5 MacFarland) was prepared, diluted in Muller-Hinton broth, incubated in the susceptibility panel containing different colistin concentrations (range 0.125-64 mg/L) with a fluorescent probe and incubated 1 h at 35ºC. After that, a flow cytometry analysis using CytoFLEX (Beckmam) was performed. Using a dedicated software (BioFAST) an automated MIC result was obtained after 1.5 h. Performance evaluation was performed according to the ISO standard 20776-2. Reproducibility and repeatability, categorical (CA) and essential agreement (EA), and lot-to-lot variation and operator-to-operator variability, as well as time to results were determined. Results: Overall, 100% CA (CI 97-100%) and 95.7% EA (CI 90-98%) was obtained with high repeatability (100%; CI 80-100%)and reproducibility (97%; (CI 83-99%)). Absence of lot-to-lot variations or differences in the operators' performance was observed. Conclusions: FASTcolistin MIC is an accurate, reliable and ultra-rapid method (1 h incubation versus 24 h) for susceptibility testing of colistin of common Gram-negative bacilli recovered in clinical laboratories.